Spontaneous baroreflex sensitivity in young normotensive African-American women - Latchman, Peter; Gates, Gregory J; Axtell, Robert S; Pereira, Jason; Bartels, Matthew N; Meersman, Ronald Edmond De (Clinical Autonomic Research, 2013)
Keywords: African American; European American; adult; article; body mass; breathing rate; clinical article; controlled study; dept.hms; diastolic blood pressure; family history; female; human; hypertension; physical activity; pressoreceptor reflex; race difference; systolic blood pressure

Make your own fitness: the suspension training project - Rauschenbach, Jim; Morrell, Katie; Ridley, Ben; Walsh, Brittany (Strategies: a journal for physical and sport educators, 2013)
Keywords: dept.hms

Promoting physical activity for elders with compromised function: the Lifestyle Interventions and Independence for Elders (LIFE) Study physical activity intervention - Rejeski, W. Jack; Axtell, Robert; Fielding, Roger; Katula, Jeffrey; King, Abby C.; Manini, Todd M.; Marsh, Anthony P.; Pahor, Marco; Rego, Alvito; Tudor-Locke, Catrine; Newman, Mark; Walkup, Michael P.; et al. (Clinical Interventions in Aging, 2013)
The Lifestyle Interventions and Independence for Elders (LIFE) Study is a Phase III randomized controlled clinical trial (Clinicaltrials.gov identifier: NCT01072500) that will provide definitive evidence regarding the effect of physical activity (PA) on major mobility disability in older adults (70-89 years old) who have compromised physical function. This paper describes the methods employed in the delivery of the LIFE Study PA intervention, providing insight into how we promoted adherence and monitored the fidelity of treatment. Data are presented on participants' motives and self-perceptions at the onset of the trial along with accelerometry data on patterns of PA during exercise training. Prior to the onset of training, 31.4% of participants noted slight conflict with being able to meet the demands of the program and 6.4% indicated that the degree of conflict would be moderate. Accelerometry data collected during PA training revealed that the average intensity - 1,555 counts/minute for men and 1,237 counts/minute for women - was well below the cutoff point used to classify exercise as being of moderate intensity or higher for adults. Also, a sizable subgroup required one or more rest stops. These data illustrate that it is not feasible to have a single exercise prescription for older adults with compromised function. Moreover, the concept of what constitutes “moderate” exercise or an appropriate volume of work is dictated by the physical capacities of each individual and the level of comfort/stability in actually executing a specific prescription.
Keywords: Accelerometry; Aged; Aged, 80 and over; Aging; Compromised physical function; Exercise; Female; Health Promotion; Humans; Independent Living; Male; Mobility Limitation; Older adults; Physical disability; Qualitative Research; Risk Reduction Behavior; Sex Distribution; accelerometry; aged; aging; article; autoregulation; body mass; compromised physical function; computer interface; computer program; conceptual framework; controlled study; dept.hms; education; elderly care; ethnicity; exercise intensity; female; health education; human; human experiment; lifestyle; male; motor performance; normal human; older adults; phase 3 clinical trial; physical activity; physical capacity; physical disability; quality of life; randomized controlled trial; semi structured interview; sex difference; social behavior; social environment

“The greatest game ever”: swatball - Swartz, Daniel R; Rauschenbach, Jim (Strategies: a journal for physical and sport educators, 2013)
Keywords: dept.hms